Nuclear Magnetic Resonance : 40: Volume 40. - Kamienska-Trela, Krystyna (Specialist periodical report., 2011)
As a spectroscopic method, nuclear magnetic resonance (NMR) has seen spectacular growth, both as a technique and in its applications. Today's applications of NMR span a wide range of scientific disciplines, from physics to biology to medicine. Each volume of Nuclear Magnetic Resonance comprises a combination of annual and biennial reports which together provide comprehensive coverage of the literature on this topic. This Specialist Periodical Report reflects the growing volume of published work involving NMR techniques and applications, in particular NMR of natural macromolecules, which is covered in two reports: NMR of Proteins and Nucleic Acids and NMR of Carbohydrates, Lipids and Membranes. In his foreword to the first volume, the then editor, Professor Robin Harris announced that the series would be a discussion on the phenomena of NMR and that articles will be critical surveys of the literature. This has certainly remained the case throughout the series, and in line with its predecessors, Volume 40 aims to provide a comprehensive coverage of the relevant NMR literature. For the current volume this relates to publications appearing between June 2009 and May 2010 (the nominal period of coverage in volume 1 was July 1970 to June 1971). Compared to the previous volume there are some new members of the reporting team. Theoretical Aspects of Spin-Spin Couplings are covered by J. Jazwinski, while E. Swiezewska and J. Wójcik provide an account of NMR of Carbohydrates, Lipids and Membranes.